Grammatical Cohesion in Sports Discourse: A Dissection of Selected Radio Programmes in Ibadan Metropolitan Area, Nigeria - Alolade, Adewole Oluwaseun (SALEE: Study of Applied Linguistics and English Education, 2024)
There is rarely any radio station that do not present programme on sports in the contemporary age. Most radio stations have their sports analysis in the various languages that their prospective listeners understand. It is possible because the issue of sports had become inevitable to the people irrespective of age, colour, and gender. It has become a unifying force among people of varied background. This, therefore, necessitated linguistic investigation into the grammatical properties utilized by sports analysts in their presentations on the radio. The study examines the occurrence of each grammatical property in enhancing cohesion in the presentations made by sports presenters on the radio stations. These grammatical devices include: reference, substitution, ellipsis, and conjunction. Ferdinand Saussures Model of Language Structure on Syntagmatic Relation was utilized as the theoretical framework for the study. The data for analysis in the study comprised thirty sports presentations that were recorded and afterwards transcribed to examine the manifestations of the grammatical devices. The results from the analyses show that personal reference is the most prominent of all the types of reference. Nominal substitution and nominal ellipsis are the most recurrent of the types of substitution and ellipsis respectively. The striking manifestations of coordinating, subordinating, and additive conjuncts dominate the types of conjunction employed by the sports analysts on the radio. The study suggests that radio analysts should continually undergo programmes that will enhance their grammatical competence and as well see language as a weapon for expressing content and meaning by practically influencing their listener. Key Words: Conjunction, Discourse, Ellipsis, Grammatical Cohesion, Reference, Substitution,